Atherosclerosis imaging using PET: Insights and applications. (14th November 2019) - Sriranjan, Rouchelle S.; Tarkin, Jason M.; Evans, Nicholas R.; Le, Elizabeth P.V.; Chowdhury, Mohammed M.; Rudd, James H.F.
Abstract : PET imaging is able to harness biological processes to characterise high‐risk features of atherosclerotic plaque prone to rupture. Current radiotracers are able to track inflammation, microcalcification, hypoxia, and neoangiogenesis within vulnerable plaque. 18 F‐fluorodeoxyglucose ( 18 F‐FDG) is the most commonly used radiotracer in vascular studies and is employed as a surrogate marker of plaque inflammation. Increasingly, 18 F‐FDG and other PET tracers are also being used to provide imaging endpoints in cardiovascular interventional trials. The evolution of novel PET radiotracers, imaging protocols, and hybrid scanners are likely to enable more efficient and accurate characterisation of high‐risk plaque. This review explores the role of PET imaging in atherosclerosis with a focus on PET tracers utilised in clinical research and the applications of PET imaging to cardiovascular drug development.